Enhanced stability and electrocatalytic activity of graphene on copper-nickel alloys for hydrogen production from wastewater. (May 2020) - Oh, Inhwan; Youn, Jong-Sang; Kang, Hari; Manavalan, Kovendhan; Jung, Sang-Chul; Park, Young-Kwon; Jeon, Ki-Joon
Abstract: Water splitting from wastewater has been in the limelight because it has advantages which are hydrogen production and electrochemical oxidation at the same time. For efficient water splitting even in wastewater condition, water splitting electrodes should have cost-effectiveness and high durability. Here, we fabricated highly stable and electrocatalytic graphene on copper-nickel alloy to electrochemically produce hydrogen from wastewater in presence of carbon layer between nickel and copper. The electrode fabrication was performed by alloying the copper with nickel and growing graphene on the surface at the same time. The copper and nickel contents of electrode surface were kept by carbon layer hindering the metal diffusion at high temperature. Highly electrocatalytic activity (onset potential = 95 and 158 mV, Tafel slope = 58 and 80 mV dec −1 ), high durability and pH independence of graphene on copper-nickel alloy were confirmed in acidic and alkaline wastewater containing formaldehyde. Graphical abstract: Image 1